2012
DOI: 10.1098/rstb.2011.0240
|View full text |Cite
|
Sign up to set email alerts
|

Repression of early lateral root initiation events by transient water deficit in barley and maize

Abstract: The formation of lateral roots (LRs) is a key driver of root system architecture and developmental plasticity. The first stage of LR formation, which leads to the acquisition of founder cell identity in the pericycle, is the primary determinant of root branching patterns. The fact that initiation events occur asynchronously in a very small number of cells inside the parent root has been a major difficulty in the study of the molecular regulation of branching patterns. Inducible systems that trigger synchronous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…Previous work has shown that under water-limiting conditions, LR development is strongly suppressed (16). Severe water limitation induces ABA signaling, which is known to inhibit the development of LRs (17).…”
Section: Patterning Of Root Tissues Is Determined By the Local Availamentioning
confidence: 99%
“…Previous work has shown that under water-limiting conditions, LR development is strongly suppressed (16). Severe water limitation induces ABA signaling, which is known to inhibit the development of LRs (17).…”
Section: Patterning Of Root Tissues Is Determined By the Local Availamentioning
confidence: 99%
“…Research on Arabidopsis and a few model crops has led to substantial knowledge of the molecular and cell biology of lateral root initiation and growth [19,20] (see also [21][22][23][24]). Since lateral roots represent the most common type of root branching and, in most cases, the majority of root length, these advances portend applied approaches to harness these pathways to develop improved cultivars.…”
Section: Lateral Roots and Root System Architecturementioning
confidence: 99%
“…The architecture of the root system, that is its three-dimensional shape, largely derives from the distribution and diversity of individual root apical meristems [2], which continuously sense and adjust their growth according to their local environment [3]. In addition, the formation of lateral roots also contributes strongly in shaping root systems and impacts soil resources capture [4].…”
Section: Introductionmentioning
confidence: 99%